1994
DOI: 10.1177/095632029400500201
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Acyclic Nucleoside Phosphonate Analogues on Hepatitis B Virus DNA Synthesis in HB611 Cells

Abstract: SummaryBy using an assay system based on a human hepatoblastoma cell line (HB611) that continuously synthesizes hepatitis B virus (HBV) DNA, 56 acyclic nucleoside phosphonate analogues were examined for their inhibitory effects on HBV DNA synthesis. The following compounds were found to inhibit HBV DNA synthesis at concentrations that were significantly lower than their minimum cytotoxic concentrations; 9-(2-phosphonylmethoxyethyl)adenine (PMEA), 9-(2-phosphonylmethoxyethyl) guanine(PMEG), 9-(2-phosphonylmetho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 22 publications
2
22
1
Order By: Relevance
“…Yokota et al (17,18) was also similar to previously reported data (18). However, the EC50 values that we obtained for PMEG and PMEGEE were much lower than those obtained by others, and the EC50 value of PMPA was higher than that of the Southern blot analysis (18).…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…Yokota et al (17,18) was also similar to previously reported data (18). However, the EC50 values that we obtained for PMEG and PMEGEE were much lower than those obtained by others, and the EC50 value of PMPA was higher than that of the Southern blot analysis (18).…”
Section: Resultssupporting
confidence: 54%
“…However, the EC50 values that we obtained for PMEG and PMEGEE were much lower than those obtained by others, and the EC50 value of PMPA was higher than that of the Southern blot analysis (18). The selective indexes of (S)-HPMPC and araA estimated by this assay system were higher than previous results (17,18). However, these differences should pose no problem in the screening of anti-HBV compounds.…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…Moreover, PMEA showed potent and selective anti-retrovirus activity in several animal models including MSV infection in newborn NMRI mice (Balzarini et al, 1989(Balzarini et al, , 1991, FIV infection in cats (Hartmann et al, 1993) and SIV infection in rhesus monkeys (Egberink et al, 1990;Tsai et al, 1994). Interestingly, PMEA has also shown activity against human and duck hepatitis B virus in human HB611 and Hep G2 2.2.15 cells and in primary duck hepatocyte cultures at 0.2 and 1.2 J..lM, respectively (Heijtink et al, 1993;Yokota et al, 1994). PMEA has recently entered clinical Phase 1/11 trials in AIDS patients.…”
Section: Introductionmentioning
confidence: 99%